THE STRUCTURAL STRATEGIES IN THE TRANSLATION OF “LITTLE SUSHINE BILINGUAL BOOK” - Cut Aja Fathin Aliyah (Universitas Negeri Medan, 2022)
The objectives of this research were (1) to find out the types of structural strategies are used to translate the “Little Sunshine Bilingual Book” (2) to find out the dominant types of structural strategies in the “Little Sunshine Bilingual Book” and (3) to find out the process of structural strategies in the “Little Sunshine Bilingual Book”. The research was conducted by using descriptive qualitative research. The data of this research were word, phrase, and sentence on the folklore of Little Sunshine Bilingual Book (2007) as source of data. The data were analyzed by using structural strategies based on Suryawinata and Hariyanto’s (2003) and process of translation based on Nababan (1999). The result of this research were (1) the types of structural strategies were 13 addition (38%), 4 subtraction (11%), 17 transposition (50%). (2) the dominant types of structural strategies is transposition (50%). (3) the process of structural strategies were analyzing, transferring, and reconstructing.Keywords: Structural strategies, translation, folklore, process of translation